Modern methods for assessing blood loss in childbirth and diagnosing postpartum hemorrhage: A review - Tatiana E. Belokrinitskaya; Anastasia G. Sidorkina; Viktor A. Mudrov (IP Berlin A.V., 2024)
Postpartum hemorrhage (PPH) is one of the leading causes of maternal mortality in Russia and worldwide. Accurate calculation of circulating blood volume (CBV) and personalized estimation of the extent of blood loss (EBL) play vital roles in the early diagnosis of PPH. Visual assessment of BL in childbirth is an available diagnostic method, but it has a high error rate compared to the gravimetric method. A dynamic assessment of the shock index (SI) as an indicator that reflects hemodynamic disorders early enough can be used as an additional diagnostic method for PPH and a test that allows predicting the need for transfusion of blood products. Aim. To review current literature on the assessment of BL in childbirth and the diagnosis of PPH. Materials and methods. The search for publications by Russian and foreign authors was carried out in the information electronic databases PubMed, PubMed Central, Scopus, MEDLINE, ScienceDirect, Cochrane Library, and eLibrary from 2016 to January 2024 using the keywords "obstetric blood loss," "PPH," and "SI." Results. When assessing the CBV, its correlation with the body mass index was revealed. Subjective methods for the PPH assessment have a large margin of error, which does not depend on the experience and seniority of the healthcare provider. The gravimetric method is more accurate, but it can underestimate the clinical situation when physiological blood loss is exceeded. Dynamic assessment of SI is an early marker of hemodynamic disorders and makes it possible to identify patients with a high risk of adverse outcomes more reliably than other parameters. Conclusion. In order to provide timely and adequate emergency medical care for excessive obstetric blood loss, a personalized approach should be used to calculate the EBL, taking into account the woman's body mass index, as well as a systematic assessment of the BL, including at least the extent of blood loss and monitoring of the SI.